The culture of poet and its effect on a poetic environment - Ahmed Abed Al-Hussain Abedallah (Assist. lecture) (Genius Journals, 2023)
I mentioned in my research to culture of poets and the difference between them in abilities into the style of poetry and its effects on culture of environment of poetry that the poet lived .we took a sample Abo Tammam Al Taie and his effects on poets through his method ,he depended on discovering and imagination in his poetries .This culture encouraged many poets to revolt on classic methods in writing poetries and some of them went into renew in subjects and appear new types like shabi poetry .I mentioned to Abo Tammam as a sample and this position on only Abasi age but many of poets like Al Matanbi , AL Saiab and Al Jawahiri .
Keywords: poets; culture; poetic environment; AL Saiab and Al Jawahiri